PERAN FORUM PENGUSAHA MUDA NAHDHIYYIN (F-PMNI) DALAM RECOVERY PEREKONOMIAN KABUPATEN BONE PADA ERA NEW NORMAL - Musrini Muis (Islamic Economic and Business Journal, 2021)
One of the communities or associations of youth entrepreneurs in Bone is the Nahdhiyyin Indonesia Youth Entrepreneurs Forum (F-PMNI). The presence of F-PMNI is also expected to be able to play a role in economic recovery in Bone in the new normal era. This study aims to provide a description and description of the role played by youth nahdhiyyin entrepreneurs in Bone in economic recovery and becoming more responsive to changes in the business climate during the new normal. This study used a type of field research with a descriptive qualitative approach. The results of research related to the role of F-PMNI in the economic recovery of Bone district in the new normal era, namely Providing education for business actors, Providing capital assistance for business development, As innovators in their contribution to economic development, entrepreneurs looking for sources of innovation, paying close attention to changes -changes that occur, calculate opportunities, and plan innovations to be carried out, Act as a Risk Taker, and the presence of F-PMNI is also expected to be able to become a liaison between the community or business actors with the government so that synergy and good partners can be established, so that the economic recovery able to walk well. Salah satu komunitas atau lembaga perkumpulan pengusaha muda yang ada di Kabupaten Bone, yaitu Forum Pengusaha Muda Nahdhiyyin Indonesia (F-PMNI). Kehadiran F-PMNI juga diharapkan mampu berperan dalam recovery perekonomian di Kabupaten Bone pada era new normal. Penelitian ini bertujuan untuk memberikan deskripsi dan gambaran terkait peran yang dilakukan oleh para pengusaha muda nahdhiyyin di Kabupaten Bone dalam recovery perekonomian dan menjadi lebih responsif terhadap perubahan iklim bisnis pada masa new normal. Penelitian ini menggunakan jenis penelitian lapangan dengan pendekatan kualitatif deskripstif. Adapun hasil penelitian terkait peran F-PMNI dalam recovery perekonomian kabupaten Bone pada era new normal, yaitu Memberikan edukasi bagi para pelaku usaha, Memberikan bantuan permodalan untuk pengambangan usaha, Sebagai inovator dalam kontribusinya atas pembangunan ekonomi, pengusaha mencari sumber inovasi, memperhatikan dengan seksama perubahan-perubahan yang terjadi, melakukan kalkulasi peluang, serta merencanakan inovasi yang akan dilakukan, Berperan sebagai Risk Taker, dan Kehadiran F-PMNI juga diharapkan mampu menjadi penghubung masyarakat atau para pelaku usaha dengan pemerintah agar mampu terjalin sinergitas dan mitra yang baik, sehingga recovery perekonomian mampu berjalan dengan baik.